386 LAPAROSCOPIC HELLERS MYOTOMY AND ANGLE OF HIS ACCENTUATION FOR ACHALASIA CARDIA: 10 YEARS EXPERIENCE FROM A SINGLE SURGICAL CENTRE. (14th September 2020) - Parshad, R; Singla, V; Suhani, S; Bhattacharjee, H; Makharia, G; Sharma, R
Abstract:  : Achalasia is a rare disease with Laparoscopic Hellers cardio-myotomy (LHCM) being the gold standard surgical modality. An antireflux procedure is required along with myotomy to decrease the chances of reflux postoperatively. We have performed Angle of His Accentuation (AOH) as an anti-reflux procedure in 126 patients who underwent LHCM since 2010. This study presents the symptomatic and objective outcomes of LHCM with AOH. Methods: Review of prospectively collected data of patients with Achalasia cardia undergoing LHCM with AOH from 2010–2019. Subjective symptoms were scored for dysphagia, heartburn, regurgitation and quality of life using scoring systems mentioned in table 1 and Achalasia specific health related Quality of life questionnaire (ASHRQoL). Objective tests included Timed Barium swallow, Endoscopy and high-resolution manometry. Patients were evaluated in pre and postoperative period at regular intervals. Success was defined as follows: Eckardt score of ≤3, Dysphagia score of 0/1, Regurgitation and heartburn score of 0, >50% clearance on timed barium swallow, IRP <15 and absence of esophagitis. Results: 126 patients were operated during the study period with no mortality or conversion. Mean age was 33.5(years), symptom duration 49.8(months), 31 had preoperative dilatation. The mean operative time was 131 (minutes). Subjective outcome was available in all patients & objective data in 66. At median follow of 31 months (IQR 15–59) outcomes significantly improved (Table 1) with 93% having dysphagia relief. 14 (11%) had new onset heartburn; 6(4.7%) needed regular proton pump inhibitors. ASHRQoL improved significantly (59.51 to 19.57). Pre&post-operative IRP, Timed Barium and endoscopy available in 66, 39 and 62 patients improved significantly. 6(9.6%) patients had endoscopic evidence of esophagitis (LA-A 3, B/C 3). Conclusion: Laparoscopic Heller myotomy with Angle of His accentuation is safe simple and effective procedure for Achalasia cardia. It provides significant relief of symptoms, improvement in quality of life and improvement in objective parameters. Post- operative heartburn and esophagitis is acceptable. We recommend Angle of His accentuation as an adjunct to Laparoscopic Heller myotomy.